A direct borohydride fuel cell with a polymer fiber membrane and non-noble metal catalysts - Yang, Xiaodong (Nature Publishing Group, 2012)
Polymer electrolyte membranes (PEM) and Pt-based catalysts are two crucial components which determine the properties and price of fuel cells. Even though, PEM faces problem of fuel crossover in liquid fuel cells such as direct methanol fuel cell (DMFC) and direct borohydride fuel cell (DBFC), which lowers power output greatly. Here, we report a DBFC in which a polymer fiber membrane (PFM) was used, and metal oxides, such as LaNiO(3) and MnO(2), were used as cathode catalysts, meanwhile CoO was used as anode catalyst. Peak power density of 663 mW·cm(−2) has been achieved at 65°C, which increases by a factor of 1.7–3.7 compared with classic DBFCs. This fuel cell structure can also be extended to other liquid fuel cells, such as DMFC.